2011
DOI: 10.4049/jimmunol.1004111
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Endoplasmic Reticulum Stress Are Coregulated by Crocin To Prevent Demyelination and Neurodegeneration

Abstract: Endoplasmic reticulum (ER) stress is a homeostatic mechanism, which is used by cells to adapt to intercellular and intracellular changes. Moreover, ER stress is closely linked to inflammatory pathways. We hypothesized that ER stress is an integral component of neuroinflammation and contributes to the development of neurological diseases. In autopsied brain specimens from multiple sclerosis (MS) and non-MS patients, XBP-1 spliced variant (XBP-1/s) was increased in MS brains (p < 0.05) and was correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 66 publications
6
87
0
2
Order By: Relevance
“…9,6 Apoptosis after central nervous system damage occurs through an extrinsic pathway involving the Fas ligand, an intrinsic pathway through ER stress response in the rat spinal cord injury model D Matsuyama et al Figure 5 Comparison of the GRP78 expression ratio between all cell types. The highest GRP78 expression ratio was observed at the acute phase of injury followed by a gradual declining trend in all cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,6 Apoptosis after central nervous system damage occurs through an extrinsic pathway involving the Fas ligand, an intrinsic pathway through ER stress response in the rat spinal cord injury model D Matsuyama et al Figure 5 Comparison of the GRP78 expression ratio between all cell types. The highest GRP78 expression ratio was observed at the acute phase of injury followed by a gradual declining trend in all cells.…”
Section: Discussionmentioning
confidence: 99%
“…8 Since the accumulation of unfolded proteins leads to apoptosis, the enhancement of GRP78 is a possible strategy to inhibit apoptotic cell death following neurotrauma and neurodegenerative disease. 5,9,10 Excessive accumulation of abnormal proteins leads to the expression of C/EBP homologous transcription factor protein (CHOP), which is a prominent proapoptotoc protein of the ER stress response. 11,12 Understanding of the precise mechanism of ER stressmediated apoptosis in SCI may lead to the development of novel treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence to indicate that ER stress is linked to inflammation through several intersecting cellular pathways, particularly proinflammatory cytokines and reactive oxygen species. 27,63,64 Protein folding is an energy-demanding process that occurs in oxidizing conditions. 63 Many neurodegenerative diseases include inflammation and ER stress impacts inflammation.…”
Section: Fig 5 the Hippocampal Neurogenesis Is Impaired Following Smentioning
confidence: 99%
“…In addition, inflammatory gene expression, endoplasmic reticulum stress in the spinal cord, and neurobehavioral deficits were ameliorated by crocin treatment in an experimental EAE model (34). Regarding the anti-inflammatory effect of crocin, Wang et al, reported that pretreatment with crocin resulted in neuroprotective effects on traumatic brain damage, and decreased microglial activation, proinflammatory cytokine release, and apoptosis by activating Notch signaling pathway (40).…”
mentioning
confidence: 99%
“…In an experimental autoimmune encephalomyelitis (EAE) model, crocin could prevent demyelination and neurodegenerative activities (34). In addition, it has antiinflammatory effects on brain microglial cells (34,35).…”
Section: Introductionmentioning
confidence: 99%